A genetic variant within STS previously associated with inattention in boys with attention deficit hyperactivity disorder is associated with enhanced cognition in healthy adult males. Issue 3 (9th February 2017) - Humby, Trevor; Fisher, Amelia; Allen, Christopher; Reynolds, Meghann; Hartman, Annette; Giegling, Ina; Rujescu, Dan; Davies, William
Abstract: Introduction: The enzyme steroid sulfatase (STS) converts sulfated steroids to their non‐sulfated forms. Deficiency for this enzyme is associated with inattention but preserved response control. The polymorphism rs17268988 within the X‐linked STS gene is associated with inattentive, but not other, symptoms in boys with attention deficit hyperactivity disorder (ADHD). Methods: We initially tested whether rs17268988 genotype was associated with attention, response control, and underlying aspects of cognition, using questionnaires and neuropsychological tasks, in two independent cohorts of healthy adult males. In an additional analysis based upon existing data, the performance of mice with genetic or pharmacological manipulations of the STS axis under attentionally demanding conditions was investigated. Results: G‐allele carriers at rs17268988 exhibited reduced reaction time, enhanced attention, and reduced reaction time variability relative to C‐allele carriers. Mice with genetic or pharmacological manipulations of the STS axis were shown to have perturbed reaction time variability. Discussion: Our findings provide additional support for an association between rs17268988 genotype and attention, which may be partially mediated by reaction time variability; they also indicate that, in contrast to the situation in boys with ADHD, in healthy men, the G‐allele at rs17268988 is associated with enhanced cognition. As reaction time variability is a predictor of well‐being, rs17268988 genotype may represent a biomarker for long‐term health. Abstract : The G‐allele at genetic polymorphism rs17268988 within the STS gene has been associated with increased inattentive symptoms in boys with ADHD. In this paper, we show that this allele is associated with enhanced cognition, including attention, in healthy men. Our data confirm that this variant is associated with attention, and suggest that the same allele may be associated with different behavioral outcomes in different populations.